2013
DOI: 10.1260/0263-6174.31.1.17
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Cellulase Isolated from Aspergillus Niger on Chitosan/Alginate Particles Functionalized with Epichlorohydrin

Abstract: This work investigates the adsorption of cellulase (isolated from Aspergillus niger) in a fixed-bed column using chitosan/alginate particles functionalized with epichlorohydrin (Cs/Ag-E) as the adsorbent. The particles were prepared and characterized with respect to apparent density, particle porosity, particle size, surface chemistry and thermal stability. Cellulase solutions were prepared in sodium citrate buffer (20 mM) at pH 5. Several breakthrough curves were obtained by varying the flow rate and feed con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 39 publications
1
4
0
Order By: Relevance
“…In addition, the bands at 1617 and 1417 cm −1 are assigned to asymmetric and symmetric stretching peaks of Alg carboxyl groups. The peak at 3000 cm −1 corresponds to the hydroxyl groups of GG and Alg polysaccharides [10,12]. These results confirm the success of the cross-linking reaction.…”
Section: Physicochemical Characterization Of the Matrixsupporting
confidence: 74%
See 1 more Smart Citation
“…In addition, the bands at 1617 and 1417 cm −1 are assigned to asymmetric and symmetric stretching peaks of Alg carboxyl groups. The peak at 3000 cm −1 corresponds to the hydroxyl groups of GG and Alg polysaccharides [10,12]. These results confirm the success of the cross-linking reaction.…”
Section: Physicochemical Characterization Of the Matrixsupporting
confidence: 74%
“…However, there are few reports on enzyme adsorption capacity onto these matrixes, especially about the potential application of these systems in the scale up of protein isolation. Rodriguez et al [10] studied the adsorption of cellulase in batch and column using a mixture of two polyelectrolytes of opposite electrical charge −chitosan and Alg-and reported an enzymatic recovery of 29%. This low yield can be due to a decrease in the number of positive charges of chitosan through the interaction with Alg negative charges.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the CHS-GLUT matrix has a grooved surface and the CHS-EPO matrix exhibits a rough surface. Other authors have reported that an increased roughness at the matrix surface could contribute to increased adsorption of biomolecules [29].…”
Section: Matrices Surface Morphologymentioning
confidence: 99%
“…Other authors [29] have studied the adsorption of cellulase isolated from A. niger using chitosan/alginate particles functionalized with epichlorohydrin as the adsorbent. They reported an enzyme elution percentage of only 30%, being one-third of the percentage obtained in this work.…”
Section: Evaluation Of Chitosan Matrices For Adsorption Of Endoglucan...mentioning
confidence: 99%
“…Adsorption equilibrium constitutes a fundamental concept in the adsorption science, which assumes that there is a well-defined relationship between the amount of adsorbed material and the concentration in the bulk phase (Dabrowski 2001). Determination of the proper adsorption equilibrium model and respective parameter values constitutes an essential step for characterization and evaluation of adsorbents and for development and design of industrial processes, including water treatment, drying of natural and cracked gases, separation of aromatics, purification of gaseous streams and separation and purification of proteins, among many other applications (Yang 1997;Dabrowski 2001;Rodrigues et al 2013). The commonest industrial adsorbents are activated carbon, silica gel, alumina and zeolites (Do 1998;Dabrowski 2001).…”
Section: Introductionmentioning
confidence: 99%